Management System of Risk Events and Situation Prediction - Josef DVORÁK; Stanislav HOSNEDL (Communications of International Proceedings, 2021)
Although there are a lot of engineering design methodologies or  methods implemented in guidelines and standards which help engineering designers to reduce “reliability” and safety risks of the Designed Technical Products (TS). Their common feature is especially high dependence on specialized experience of their users, time consuming, and conceptual and terminological inconsistency resulting in very difficult compatibility with engineering designing itself. Our research has been therefore focused on risk predictions and analyses as complementary assisting processes when designing tangible technical products. Engineering Design Science and Methodology (EDSM), especially its core part Theory of Technical Systems (TTS), are being used as a basis for the developing comprehensive theory and methodology aiming at rationalization management of the mentioned activities to achieve higher risk robustness of the designed technical products considered as Technical systems (TS).
Keywords: Risk; EDSM; TTS; model